Choroid plexus papillomas are induced by c-Myc overexpression in the choroid plexus via a T-cell inflammatory mechanism. (12th October 2019) - Merve, Ashirwad; Zhang, Xinyu; Pomella, Nicola; Acquati, Serena; Hoeck, Joerg; Dumas, Anaelle; Rosser, Gabriel; Li, Yichen; Jeyapalan, Jennie; Vicenzi, Silvia; Sabò, Arianna; Sheer, Denise; et al.
Abstract: Choroid plexus tumours (CPT) account for up to 20% of brain tumours in children under 2 years of age. Histologically CPTs are classified into three categories - Choroid Plexus Papilloma (CPP), Atypical Choroid Plexus Papilloma (ACPP) and Choroid Plexus Carcinoma (CPC). Recent literature demonstrates that CPP and ACPP are molecularly distinct from CPC. Initial management for CPT include surgery followed by adjuvant therapy in selected patients. Currently there are no disease-specific chemotherapeutic agents available, possibly because of their rarity and paucity of faithful pre-clinical experimental models. In this study we show that c-Myc overexpression in the choroid plexus epithelium induces T-cell inflammation-dependent choroid plexus papillomas in a mouse model. We demonstrate that c-MYC is expressed in a substantial proportion of human choroid plexus tumours and that this subgroup of tumours is characterised by an inflammatory transcriptome and significant inflammatory infiltrates. We observed that triple transgenic compound mutant mouse model with c-Myc overexpression in an immune-suppressed background led to a decreased incidence of CPP and reduced tumour bulk. A reduced tumour size was also observed when c-Myc overexpressing mice were treated with anti-CD3 antibodies. Our data raise the possibility that benign choroid plexus tumours expressing c-MYC could be amenable to medical therapy with anti-inflammatory drugs.